2022
DOI: 10.3390/ijms23063350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endocrine Disruptors upon Non-Genetic Inheritance

Abstract: Similar to environmental factors, EDCs (endocrine-disrupting chemicals) can influence gene expression without modifying the DNA sequence. It is commonly accepted that the transgenerational inheritance of parentally acquired traits is conveyed by epigenetic alterations also known as “epimutations”. DNA methylation, acetylation, histone modification, RNA-mediated effects and extracellular vesicle effects are the mechanisms that have been described so far to be responsible for these epimutations. They may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 156 publications
1
24
0
Order By: Relevance
“…( 39 ) on the multi-generational and very probably trans-generational impact of DES on neurodevelopment. This strengthens the hypothesis that in-utero exposure to DES (and to other endocrine disruptors) contributes to the pathogenesis of psychiatric disorders, particularly autistic disorders ( 47 , 48 ). According to the theory proposed by Nilsson and Skinner ( 49 ), epigenetic alterations (epimutations) induced by environmental insults (e.g.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…( 39 ) on the multi-generational and very probably trans-generational impact of DES on neurodevelopment. This strengthens the hypothesis that in-utero exposure to DES (and to other endocrine disruptors) contributes to the pathogenesis of psychiatric disorders, particularly autistic disorders ( 47 , 48 ). According to the theory proposed by Nilsson and Skinner ( 49 ), epigenetic alterations (epimutations) induced by environmental insults (e.g.…”
Section: Methodssupporting
confidence: 85%
“…The F3 generation may exhibit transgenerational inheritance of disease susceptibility. Several epimutations can be implicated in this non-genetic inheritance ( 48 ): DNA and RNA methylation changes, histone modification alterations, non-coding RNAs and extracellular vesicles. It has been already shown that upon DES exposure, the ZFP57 and ADAMTS9 genes become hypermethylated.…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear if EVs directly control gene expression, but they may participate in the epigenetic regulation of gene expression by transporting and delivering specific molecules potentially implicated in epigenetic inheritance. This mechanism might be of relevance in the genital tract with the modification of the gamete environment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…While life-style factors such as obesity have been shown to alter sperm non-coding RNAs in men,(53) no human studies have directly investigated the link between environmental toxicants such as DDT and germline RNA changes to the best of our knowledge; though several reports in animal models exist. (5456) Nonetheless, a number of epidemiological studies link parental environmental toxins and cancer in the progeny. For instance, an association between paternal exposure to pesticides and a number of childhood cancers in offspring has been reported.…”
Section: Discussionmentioning
confidence: 99%